Impact of Petroleum Industry Activities on Basic Soil Physical and Chemical Properties: A Case Study PT Pertamina EP Cepu Bojonegoro, Indonesia - AH. Maftuh Hafidh Zuhdi; Tandaditya Ariefandra Airlangga; Irene Zaqyah (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Petroleum industrial activities have the potential to alter soil physical and chemical properties through various contamination mechanisms and operational processes. This research aimed to evaluate the impact of PT Pertamina EP Cepu petroleum industrial activities on basic physical and chemical soil properties in areas surrounding operations. The study was conducted from October to November 2025 using a descriptive survey approach with purposive sampling method. Soil samples were collected at 0-20 cm depth from 12 sampling points located within a ± 200-meter radius in four cardinal directions (North, East, South, and West) from the operational center. Physical properties analyzed included soil texture, bulk density, and porosity, while chemical properties included pH, C-Organic, total N, available P, exchangeable K, and electrical conductivity (EC). Data analysis was performed descriptively by comparing laboratory measurement results with soil property assessment criteria established by Balai Penelitian Tanah to categorize each parameter and identify soil quality degradation levels in the research area. The results showed that soil in the research area had clay texture (67% clay fraction), high bulk density (1.47 ± 0.21 g/cm³), moderate porosity (44.5%), neutral pH (6.7 ± 0.2), very low C-Organic (0.99 ± 0.07%) and total N (0.07 ± 0.01%), high available P (28.64 ± 2.22 mg/kg) and exchangeable K (0.94 cmol(+)/kg), and moderately high EC (3.9 dS/m). These findings indicate that petroleum operational activities have caused soil quality degradation, particularly through soil compaction and reduction in organic matter content. Appropriate soil management interventions, including organic matter addition, traffic management, and contamination remediation, are essential to restore and maintain soil quality in petroleum operational areas.